EVALUASI PELAKSANAAN PEMBANGUNAN RUANG KELAS BARU DENGAN CARA SWAKELOLA PADA SMKN MANONJAYA DAN SMK HARAPAN KITA - , Kurniawan, Prof. Suyanto, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The development of new self managed classroom in a vocational high school aims to provide an education infrastructure in the form of building to guarantee the availability of high level education services especially in vocational high school. This research aims to evaluate the development of new self-managed classroom in Manonjaya and Harapan Kita high schools. The evaluation is conducted by identifying the factors supporting and hindering the development of the self managed classrooms, analyzing the strategy through SWOT analysis, and deciding the Key Success Factors in development of new self-managed classrooms in Manonjaya and Harapan Kita high schools. The implementation of new self-managed classrooms has worked well but there are differences in completion time. Manonjaya high school can accomplish the development in 86 days whereas Harapan Kita in 132 days. The KSFs in the implementation include: commitment from local government in this case district head / the mayor